Analysis of the Relationship between UGC’s Concrete, Abstract Content, and Brand Attitude on Purchase Intention of Generation Z - Praphruetmon, Chenicha; Tubtimcharoon, Nata; Sresteesang, Witwasit; Sriaphiphan, Phatsanan (Journal of ASEAN PLUS Studies, 2025)
In this fast-paced era, social media is becoming an increasingly important part of brand-customer communication, especially for Generation Z, whose activities are mostly conducted online. Therefore, this study conducted a 1x2 experiment with Generation Z participants, —200 participants for UserGenerated Content (UGC) abstract content and 210 for in User-Generated Content (UGC) concrete content—to examine how User-Generated Content (UGC) aﬀects purchas intention. The results show that when consumers use social media to search for product information, the dissemination of their User-Generated Content (UGC), concrete content, and abstract content has a significant positive correlation with purchase intention, and brand equity has a significant positive correlation with purchase intention. The mediating role analysis of brand equity is eﬀective with the purchase intention of User-Generated Content (UGC).